2012
DOI: 10.1038/ki.2011.341
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant therapy in hemodialysis patients: a systematic review

Abstract: Antioxidants have been used as therapies to decrease oxidative stress and improve CVD risk in hemodialysis (HD) patients. A systematic search of the Medline database (search date 30 April 2011) found 56 studies investigating the effects of antioxidant therapies on biomarkers of oxidative stress (53 studies) or clinical outcomes (3 studies). The majority were small trials using a nonrandomized open-label design with a single HD group (no HD controls). Alpha-tocopherol was the most investigated antioxidant, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 89 publications
(101 reference statements)
3
74
0
12
Order By: Relevance
“…Despite evidence for harmful effects in the general population of high doses of some common supplements (β-carotene, vitamin E, vitamin A) [50,51], there is evidence, although limited, that chronically haemodialysed patients could benefit from the use of antioxidants to prevent cardiovascular complications [52,53]. However, there are also some contradictory findings which suggest that the mechanism and consequences of oxidative damage in ESRD need closer examination before antioxidant interventions are evaluated [54].…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence for harmful effects in the general population of high doses of some common supplements (β-carotene, vitamin E, vitamin A) [50,51], there is evidence, although limited, that chronically haemodialysed patients could benefit from the use of antioxidants to prevent cardiovascular complications [52,53]. However, there are also some contradictory findings which suggest that the mechanism and consequences of oxidative damage in ESRD need closer examination before antioxidant interventions are evaluated [54].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have documented mortality prediction by oxidative stress in dialysis patients (14)(15)(16)(17) and antioxidant therapy in dialysis patients to reduce CVD has in general been unsuccessful (40); however, two studies reported a positive effect of interventions targeting oxidative stress (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…These data highlight the uncertainties surrounding the use of antioxidants in patients receiving dialysis. Although .50 studies investigating antioxidants in patients undergoing hemodialysis have been published, there is no consensus on procedures for optimal study design, and no previous studies have measured both appropriate biomarkers and clinical outcomes in sufficiently large populations to draw meaningful conclusions (reviewed in Coombes and Fassett 39 ). Further studies, probably using different antioxidants and perhaps assessing different endpoints, are warranted to fully test whether antioxidants may confer benefit to this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the suggestion that oxidative stress pathways are a "nontraditional" cardiovascular risk factor for patients receiving dialysis therapy and that antioxidant therapies may be more effective in this population than in studies of primary and secondary risk prevention in the absence of advanced kidney disease. 39 We chose to study a combination of mixed tocopherols and ALA as antioxidant therapy for several reasons. First, in two separate pilot studies, the separate provision of a-tocopherol and the thiol-containing antioxidant N-acetyl cysteine had some benefit in reducing cardiovascular events rates in patients receiving MHD.…”
Section: Discussionmentioning
confidence: 99%